Writing guide and projects manual to accompany Living with Art - Gilbert, Rita, 1942- 4 0 16; 5 (New York : McGraw-Hill)
Writing about art: basics - Looking at art - Thinking about art - Writing essentials - Writing refinements - Outlining - Comparing and contrasting - Design analysis - Speaking about art.
Pronunciation guide, Time line chart and Design overlays are filed in Workroom Stack.
Keywords: 2 -- 0; 6; Art appreciation; 20; 2